Water Quality Test of the River in the Campus Area of Universitas Negeri Padang in a Simple Way - Fristia, Yolla (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
The UNP campus area is crossed by a river that flows from the Basko area to Muaro Gantiang Beach, and this river is known as the